Direct transfer of frozen-thawed bovine embryos and its application in cattle reproduction management - Osamu DOCHI (The Journal of Reproduction and Development, 2019)
Embryo transfer entails many procedures and techniques, of which embryo freezing is an important component in bovine embryo transfer. Embryo freezing techniques have been developed over the last 40 years, allowing practical availability, and have become essential for cattle reproduction management under field conditions. The direct transfer methods of frozen-thawed, in vivo-derived, and in vitro-produced (IVF) bovine embryos using 1.5 M ethylene glycol (EG) with or without sucrose (SUC) are used widely under on-farm conditions, not only in Japan but also globally. The direct transfer method using 1.5 M glycerol (GLY) and 0.25 M SUC (GLY-SUC) is used mainly in Japan. The pregnancy rate with direct transfer of frozen-thawed bovine embryos in either EG or GLY-SUC has been found to not differ from conventional freezing with GLY and traditional dilution techniques. Pregnancy rates following direct transfer of frozen-thawed bovine embryos were affected by the developmental stage of the embryos and the parity of the recipients. The use of ultrasound-guided on-farm ovum pickup is ushering in a new revolution for the commercial application of IVF embryos. Globally, for the first time more IVF bovine embryos were transferred in 2017 than produced in vivo. More than 60% of IVF embryos were transferred fresh due to a low pregnancy rate of frozen-thawed IVF embryos. Many factors seemed to be involved in improving the survival rate of frozen-thawed IVF embryos. Therefore, further research is needed to improve the freezing tolerance of IVF embryos to develop efficient direct transfer methods analogous to those used for in vivo embryos.